Does the STAF score help detect paroxysmal atrial fibrillation in acute stroke patients? - Horstmann, Solveig; Rizos, Timolaos; Güntner, Janina; Hug, Andreas; Jenetzky, Ekkehart; Krumsdorf, Ulrike; Veltkamp, Roland (European journal of neurology, 2013)
Background and purpose Detecting paroxysmal atrial fibrillation (pAF) soon after acute cerebral ischaemia has a major impact on secondary stroke prevention. Recently, the STAF score, a composite of clinical and instrumental findings, was introduced to identify stroke patients at risk of pAF. We aimed to validate this score in an independent study population. Methods Consecutive patients admitted to our stroke unit with acute ischaemic stroke were prospectively enrolled. The diagnostic work-up included neuroimaging, neuroultrasound, baseline 12-channel electrocardiogram (ECG), 24-h Holter ECG, continuous ECG monitoring, and echocardiography. Presence of AF was documented according to the medical history of each patient and after review of 12-lead ECG, 24-h Holter ECG, or continuous ECG monitoring performed during the stay on the ward. Additionally, a telephone follow-up visit was conducted for each patient after 3 months to inquire about newly diagnosed AF. Items for each patient-age, baseline NIHSS, left atrial dilatation, and stroke etiology according to the TOAST criteria - were assessed to calculate the STAF score. Results Overall, 584 patients were enrolled in our analysis. AF was documented in 183 (31.3%) patients. In multivariable analysis, age, NIHSS, left atrial dilatation, and absence of vascular etiology were independent predictors for AF. The logistic AF-prediction model of the STAF score revealed fair classification accuracy in receiver operating characteristic curve analysis with an area under the curve of 0.84. STAF scores of ≥5 had a sensitivity of 79% and a specificity of 74% for predicting AF. Conclusion The value of the STAF score for predicting the risk of pAF in stroke patients is limited.